Properties of Raphia Palm Interspersed Fibre Filled High Density Polyethylene - Henry C. Obasi (Advances in Materials Science and Engineering)
Blends of nonbiodegradable and biodegradable polymers can promote a reduction in the volume of plastic waste when they undergo partial degradation. In this study, properties of raphia palm interspersed fibre (RPIF) filled high density polyethylene (HDPE) have been investigated at different levels of filler loadings, 0 to 60 wt.%. Maleic anhydride-graft polyethylene was used as a compatibilizer. Raphia palm interspersed fibre was prepared by grinding and sieved to a particle size of 150 µm. HDPE blends were prepared in a corotating twin screw extruder. Results showed that the tensile strength and elongation at break of the blends decreased with increase in RPI loadings and addition of MA-g-PE was found to improve these properties. However, the Young’s modulus increased with increase in the amount of RPI into HDPE and compatibilization further increased the Young’s modulus. The water absorption indices and weight loss for RPI/HDPE composites were found to increase with RPI loadings but were decreased on addition of MA-g-PE.